2019
DOI: 10.1097/md.0000000000013940
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength can be used to evaluate postoperative residual neuromuscular block recovery in patients undergoing general anesthesia

Abstract: Background:Residual postoperative neuromuscular blockade is an important clinical issue. Neuromuscular monitoring is usually used to evaluate neuromuscular recovery in patients undergoing general anesthesia. However, this procedure is inconvenient and not widely adopted. We aimed to examine the correlation between grip strength and train-of-four ratio (TOFr) to examine whether assessing grip strength can be used clinically to monitor residual neuromuscular blockade.Methods:One hundred twenty patients with ASA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Considering associations between the stressful life event and the low physical state raises the potential for a skewed rating affected by motivational and emotional aspects and psychological health [ 46 , 47 ]. Other underlying mechanisms with possible modifying effects comprise general anesthesia received [ 48 ], changes in hormone levels [ 49 ], and chronic illness with painful or weak hands [ 50 , 51 ]. The detected continuous reduced functioning requires close observance beyond the time frame chosen in this study to prevent further decline.…”
Section: Discussionmentioning
confidence: 99%
“…Considering associations between the stressful life event and the low physical state raises the potential for a skewed rating affected by motivational and emotional aspects and psychological health [ 46 , 47 ]. Other underlying mechanisms with possible modifying effects comprise general anesthesia received [ 48 ], changes in hormone levels [ 49 ], and chronic illness with painful or weak hands [ 50 , 51 ]. The detected continuous reduced functioning requires close observance beyond the time frame chosen in this study to prevent further decline.…”
Section: Discussionmentioning
confidence: 99%
“…Grip Strength: a measure of muscular strength to monitor residual neuromuscular blockade, clinically [ 12 ]. Muscular strength score (1 = keeps grip for >15 seconds and 0 = does not keep grip or keeps it for less than 15 seconds).…”
Section: Methodsmentioning
confidence: 99%
“… 2 Clinical methods do not quantify the degree of NMB, so they have been abandoned and replaced by device-based methods. 7 , 9 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these monitors is far from ideal, since studies have shown that only 10–15% of anesthesiologists routinely use neuromuscular function monitors, and only 18% reported that all workplaces are equipped with this monitor. 11 , 14 Studies on R NMB incidence at the PACU have shown results from 9% to 47%, with some publications showing even higher rates, indicating that the incidence can reach 88–93%. 3 , 4 , 5 , 9 , 15 …”
Section: Introductionmentioning
confidence: 99%